The subjunctive in Spanish - Solano, J. Miguel (Kansas Working Papers in Linguistics, 1980)
The various analyses for the subjunctive in Spanish that have been proposed can be classified into two major categories: syntactic and semantic. Syntactic analyses consist mainly of classifications of instances in which the subjunctive must be used. Semantic analyses try to give the underlying principle(s) that seem to govern the use of the subjunctive in Spanish. In this paper two examples of each major category are discussed, and a new semantic account in terms of conventional implicature is proposed. A single idea seems to account for most of the cases in which the subjunctive is used in Spanish.